Human skull 3D model development and biomechanical analysis in full frontal crash / Shahrul Hisyam Marwan - Marwan, Shahrul Hisyam (2014)
This thesis is basically divided into three main topics. The three main topics are reverse engineering approach, fmite element analysis and accident reconstruction for a case study. The study aims to reconstruct an accident reconstruction which involves a full frontal crash. It starts with reverse engineering stage. This stage describes the process of a human skull model development using reverse engineering approach to obtain the CAD data. The human skull model of actual life size is developed through the Non Contact 3D Digitizer processes. This stage involves the step-by-step process of developing a human skull to obtain CAD data. The CAD data and fmite element model development done at Computer Aided Design, Engineering and Manufacturing (CADEM) Center, Universiti Teknologi MARA, Malaysia. Then, the next stage is to do the finite element analysis from the CAD data in previous stage. In this stage, it presents the development of one degree of freedom of frontal human head impact test procedure using fmite element simulation. This study is to compare the results between simulation and experimental result conducted by Delye et al., (2007) for validation purpose. To conduct this study, the process involve is to develop finite element modeling of human skull and to analyze the data analysis which investigating the impact conditions of human skull during a human head impact on the resulting total deformation and stress distribution. There were geometric preparations, selection of elements, selection of materials, application of loadings, and the specification of boundary conditions. The last stage is to reconstruct the accident reconstruction which involves a full frontal crash. In this stage, it describes a full frontal car crash is reconstructed using finite element method to predict skull fractures. Details from the traffic and collision reports are extracted to create the computational environment. The predicted value of maximum stress is 132.01 MPa which exceeds the yield strength of human skull material. From the simulation results, it shows that the fractures are predicted at the respective velocity and initiated at the impact contact area. In summary, this study hopes to give better understanding on how to develop the three dimensional human skull model from the life size of prototype human skull as well as to do finite element analysis with the respective human skull model. This study also will help the forensic to do the prediction on the real case of accident in term of the velocity involved during the accident.